Body mass index and waist circumference: Relationship to cardiometabolic risk factors in children – Busselton Health Study 2005–2007. Issue 11 (26th June 2013) - Bell, Lana; Hung, Joseph; Knuiman, Matthew; Divitini, Mark; Beilby, John; Hunter, Michael; Mollison, Lindsay; Thompson, Peter; McQuillan, Brendan; Davis, Elizabeth
Abstract : Aim: This study aims to analyse the continuous relationship of each cardiometabolic risk factor with body mass index (BMI) and waist circumference percentiles in a population‐based sample of children. Methods: A cross‐sectional sample of 996 school children aged 6–16.9 years in Busselton, Western Australia, (2005–2007) had anthropometry and fasting blood tests for total cholesterol, high density lipoprotein, low density lipoprotein, triglycerides, glucose, insulin, high‐sensitive C‐reactive protein, liver function tests and adiponectin. Age‐ and menarche (for girls)‐adjusted means of each risk factor were related to BMI and waist circumference centiles across the full normal–overweight–obese range. Results: The correlations between BMI and waist circumference (boys 0.91 and girls 0.91) and between BMI z ‐score and waist z ‐score (boys 0.80 and girls 0.82) were high. An increase in insulin across all centile groups (for BMI and waist circumference) was found in both sexes. An increase was found for diastolic blood pressure and systolic blood pressure z ‐score, high density lipoprotein, high‐sensitive C‐reactive protein, alanine transaminase and gamma‐glutamyltransferase in only the centile groups >85% for BMI and waist circumference for both sexes. Mixed and sex‐discordant results were found for triglycerides, adiponectin and glucose. Conclusion: There are important differences in the relationships between increasing BMI/adiposity, and each comorbidity and these relationships can differ between boys and girls. This information has implications for screening and management of adiposity‐related cardiometabolic risk factors in children and for public health initiatives to reduce future burden of cardiovascular disease.